Characterization of Microbial Mat Microbiomes in the Modern Thrombolite Ecosystem of Lake Clifton, Western Australia Using Shotgun Metagenomics - Warden, John G.; Casaburi, Giorgio; Omelon, Christopher R.; Bennett, Philip C.; Breecker, Daniel O.; Foster, Jamie S. (Frontiers in Microbiology, 2016)
Microbialite-forming communities interact with the environment and influence the precipitation of calcium carbonate through their metabolic activity. The functional genes associated with these metabolic processes and their environmental interactions are therefore critical to microbialite formation. The microbiomes associated with microbialite-forming ecosystems are just now being elucidated and the extent of shared pathways and taxa across different environments is not fully known. In this study, we profiled the microbiome of microbial communities associated with lacustrine thrombolites located in Lake Clifton, Western Australia using metagenomic sequencing and compared it to the non-lithifying mats associated with surrounding sediments to determine whether differences in the mat microbiomes, particularly with respect to metabolic pathways and environmental interactions, may potentially contribute to thrombolite formation. Additionally, we used stable isotope biosignatures to delineate the dominant metabolism associated with calcium carbonate precipitation in the thrombolite build-ups. Results indicated that the microbial community associated with the Lake Clifton thrombolites was predominantly bacterial (98.4 %) with Proteobacteria, Cyanobacteria, Bacteroidetes and Actinobacteria comprising the majority of annotated reads. Thrombolite-associated mats were enriched in photoautotrophic taxa and functional genes associated with photosynthesis. Observed δ13C values of thrombolite CaCO3 were enriched by at least 3.5 ‰ compared to theoretical values in equilibrium with lake water DIC, which is consistent with the occurrence of photoautotrophic activity in thrombolite-associated microbial mats. In contrast, the microbiomes of microbial communities found on the sandy non-lithifying sediments of Lake Clifton represented distinct microbial communities that varied in taxa and functional capability and were enriched in heterotrophic taxa compared to the thrombolite-associated mats. This study provides new insight into the taxa and functional capabilities that differentiate potentially lithifying mats from other non-lithifying types and suggests that thrombolites are actively accreting and growing in limited areas of Lake Clifton.